Regulatory learning in failed thrift auctions - Gupta, Atul; Misra, Lalatendu (Journal of Banking & Finance, 2002)
We use a sample of failed thrift auctions to examine if regulators learn from early transactions and improve their performance in later transactions. Our findings suggest that experience at failure resolution does not by itself lead to improved regulatory performance. Evidence of regulatory learning is restricted to dealings with repeat acquirers; in cases where an acquiring firm makes abnormal gains, regulators are able to restructure the auction process and eliminate such gains in subsequent acquisitions made by the same acquirers.